Structural, absorption, and molecular properties of o,o'-dihydroxyazo resorcinol dyes bearing an acryloyloxy group - Özkınalı, Sevil; Çavuş, Muhammet Serdar; Ceylan, Abdullah; Gür, Mahmut (Elsevier BV, 2017)
Abstract To the best of our knowledge, this is the first study reporting the synthesis and characterization of o,o ′-dihydroxyazo dyes bearing an acryloyl group. The o,o ′-dihydroxyazo dyes were synthesized through coupling of resorcinol with the diazonium salts of 2-amino-4-methylphenol, 2-aminophenol, 2-amino-4-chlorophenol, and 2-amino-4-nitrophenol. Their acryloyl derivatives were synthesized using metallic sodium and acryloyl chloride under an inert atmosphere. Characterization of the compounds was conducted using infrared (IR), ultraviolet–visible (UV–vis), proton nuclear magnetic resonance ( 1 H NMR), and carbon nuclear magnetic resonance ( 13 C NMR) spectroscopic methods. The tautomerism of the synthesized compounds' was also evaluated. The results were compared with theoretical results obtained by density functional theory (DFT). The DFT calculations were performed to obtain ground-state optimized geometries and calculate the relevant electronic and chemical reactivity parameters. Furthermore, possible tautomers deduced from the UV–vis spectra were investigated using theoretical calculations. Both the IR and NMR spectral data showed that azo tautomers predominate in the solid state and DMSO solvent. The effects of pH, solvent, and substituent on the predominant tautomers were further investigated through UV–vis spectroscopy. The results indicate that hydrazone tautomers were dominant at pH 12 in dimethylformamide (DMF), whereas azo tautomers were dominant at pH 2 in EtOH or CHCl 3 .
Keywords: Resorcinol; Azo–Hydrazone; DFT; O,o '-Dihydroxyazo Dyes; Tautomerism